2010
DOI: 10.1021/jm901638j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Effects of Hydrogen Sulfide (H2S): Development of H2S-Releasing Drugs as Pharmaceuticals

Abstract: Gaseous transmitters are a growing family of regulatory\ud molecules involved in multilevel regulation of physiological\ud and pathological functions in mammalian tissues. Hydrogen\ud sulfide (H2S) is best known for its characteristic smell of\ud rotten eggs. It is now widely recognized that H2S, along with\ud nitric oxide (NO) and carbonmonoxide (CO), is involved in a\ud multitude of physiological functions. The generation of H2S\ud bymammalian tissues is likely to occur in a slow and constant\ud rate, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
239
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(252 citation statements)
references
References 111 publications
(113 reference statements)
2
239
0
11
Order By: Relevance
“…A number of studies suggested therapeutic potential of H 2 S-donating compounds and H 2 S gas itself for a number of animal models of human disease including ischemic brain injury (2,3).…”
Section: Physiological Levels Of H 2 S Exert Neuroprotective Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies suggested therapeutic potential of H 2 S-donating compounds and H 2 S gas itself for a number of animal models of human disease including ischemic brain injury (2,3).…”
Section: Physiological Levels Of H 2 S Exert Neuroprotective Effectsmentioning
confidence: 99%
“…Na 2 S and sodium hydrosulfide (NaHS) have been used as H 2 S donor compounds in the majority of experimental studies (2,3). However, because the half-lives of these sulfide salts are very short in biological fluid, plasma sulfide levels rapidly increase after bolus administration of Na 2 S or NaHS and then return to baseline instantaneously (5).…”
Section: Physiological Levels Of H 2 S Exert Neuroprotective Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 S -similar to the other gasotransmitters NO or CO -is water and lipid soluble and therefore also easily passes membranes. The physiology, pathophysiology, pharmacology of H 2 S particularly in the vascular system and brain has been reviewed i n a n i m p r e s s i v e a m o u n t o f r e c e n t publications (Wang 2011;Kimura 2011;Hu et al, 2011;Bucci & Cirino 2011;Wang 2010;Tan et al 2010;Gadalla & Snyder 2010;Mustafa et al, 2009;Mancardi et al, 2009;Qu et al, 2008;Li & Moore 2008;Łowicka & Bełtowski 2007;Szabó 2007;Wallace 2007;Wallace 2010;Lloyd 2006;Wang 2002;Boehning and Snyder 2003;Caliendo et al, 2010). Besides many other cellular targets H 2 S also acts on ion channels.…”
Section: Bk Channels -Modulation By Hydrogen Sulfide (H 2 S)mentioning
confidence: 99%
“…20 It has been reported that the activity of the p38 and extracellular signalregulated kinase (ERK)1/2 MAPKs is increased in lesional psoriatic skin as compared with non-lesional skin. 21,22 Many studies have been published on the involvement of hydrogen sulfide in inflammation, and evidence has been shown for both pro-or anti-inflammatory roles of H 2 S. 23,24 Recently, we have demonstrated that hydrogen sulfide can impair human keratinocytes adhesion and proliferation by impairing the activation of Raf-MEK-ERK pathway. 22 The specific interest to hydrogen sulfide derives from the potential applications of the results, as sulfur is able to penetrate the skin and a sulfur-rich balneotherapy, known to be effective in the treatment of psoriasis, 25 might turn useful in this disease.…”
mentioning
confidence: 99%